1996
DOI: 10.1126/science.271.5254.1387
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange of Impact Ejecta Between Terrestrial Planets

Abstract: models that assume stepwse mutaton of the STRP ~m p y that the varlaton of allele sizes Increases Inearly w~th tme (48) [D. 5. Godstein, A. Ruz Lnares, L. L. Cavali-Sforza, M. W. Feldman, Genetics 139, 463 (1995jl. Thus, we can est~mate R as the ratio of varances of allele szes (in base pa~rs) for alleles less than 110 bp (22 5/0.75 = 30.0), glvng a maxlmum age of 167,000 Y.B.P. Because we have considered only a slnge locus, the standard error on this varance-ratlo estmate IS high. However, the apparent lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(166 citation statements)
references
References 29 publications
(1 reference statement)
8
158
0
Order By: Relevance
“…This difference is due in part to the more densely occupied phase space of the particles, there being far less spread in the velocities. However, Gladman et al (1996) showed that the Martian meteorites on Earth also showed evidence for initial velocities near the escape velocity from Mars-a result consistent with our statement.…”
Section: Variations With Longitudesupporting
confidence: 82%
See 1 more Smart Citation
“…This difference is due in part to the more densely occupied phase space of the particles, there being far less spread in the velocities. However, Gladman et al (1996) showed that the Martian meteorites on Earth also showed evidence for initial velocities near the escape velocity from Mars-a result consistent with our statement.…”
Section: Variations With Longitudesupporting
confidence: 82%
“…Panspermia in the solar system has been studied at some length (e.g., Melosh & Tonks 1993;Gladman et al 1996;Worth et al 2013; see this last reference for a good historical review). And from observations of meteorites, some hypothesize that a fraction of life on Earth may have originated on Mars (which may have supported life sooner than the Earth (e.g., McKay et al 1996)).…”
Section: Introductionmentioning
confidence: 99%
“…the zone within which oxygenic photosynthetic organisms would live, would be sterilised within 100,000 years (Clark 2001). Although computer models suggest that rocks can potentially be transferred between Earth and Mars, for instance, in 10 years, more typical times are likely to be 10 5 to 10 7 years (Gladman et al 1996).…”
Section: Interplanetary Transfermentioning
confidence: 99%
“…Leake et al (1987) find that a considerable fraction of the total mass that impacted the terrestrial planets during the late heavy bombardment could have additionally impacted Mercury by a Vulcanoid population. In the case of scenario (ii) we would not expect the presence of such objects unless they are the result of a very recent and major impact or collision in the region, since the survival time scale near Mercury is of the order of a few Myr (Gladman et al 1996;Evans & Tabachnik 1999).…”
Section: Introductionmentioning
confidence: 99%